Packaging strategies in Gayo arabica ground coffee. Issue 1 (January 2021) - Safrizal; Fadhil, R; Nurba, D
Abstract: Coffee has become a distinctive feature of the Province of Aceh, so many shops have made coffee a commodity that is traded, packaging is one of the things that are attractive to consumers to buy coffee that is available. The packaging has several parameters that are considered, including writing design, packaging form, trademark, packaging color, packaging material and other parameters. The purpose of this study is to obtain a sequence of packaging parameters that are important to consider when making coffee packaging so that it attracts consumers. The research was conducted by direct interview with the owner and shopkeeper and questionnaires. The results showed that the trademark is the coffee consumer's first consideration in choosing packaged coffee, further researched, the trademark which included the name of a place famous for coffee became the first consideration.